Penyelidikan Fasies dan Lingkungan Pengendapan pada Singkapan Batuan Karbonat Berdasarkan Karakteristik dan Ichnofasies di Sungai Oyo, Kecamatan Wonosari, Kabupaten Gunung Kidul, DIY - Timotius Tuska, Robert; Putri, Dwiginasa; Angga Purnama, Wahyu; Abdillah Ahmad, Ghani; Flowers Rizqi, Al Hussein (Institut Teknologi Nasional Yogyakarta, 2024)
Research on Facies and Environment The deposition of carbonate rocks of the Oyo Formation is located on the Oyo River, Wonosari District, Gunung Kidul Regency, Special Region of Yogyakarta with a geographical position of 7Â°54'45.7